The impact of tourism development on local communities in Gumbrih village - Bali - Joko Adinegara; I Ketut Sirna; Putu Steven Eka Putra (Universitas Merdeka Malang, 2024)
This research aim to identify the impact of tourism development from economic, social, cultural, and environmental aspects in Gumbrih Village and has never been studied comprehensively. The qualitative method is carried out by interviewing stakeholders to obtain in-depth information. The results from observations and interviews generally concluded that the impact of tourism development in Gumbrih Village has not yet had a real impact on economic, social, cultural, and environmental aspects. This is due to the impact of the Covid-19 pandemic being felt by the community. However, from the economic aspect before the pandemic, it was able to create jobs in businesses, but the income earned was not optimal because visitors who came still relied on the local community. From the social and cultural aspects, the community is starting to realize the importance of preserving cultural heritage, especially in indigenous culture and art because it can become one of the tourist attractions that can be developed. The development of tourism regarding environmental aspects can be maintained properly, but the community is still guided by the concept of